DEVELOPMENT OF IT-BASED PAI LEARNING MEDIA - Huda, Samsul; Manshur, Umar; Khaer, Abu; Sain, Zohaib Hassan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This article aims to enable more advanced and developed learning so that learning becomes more effective and efficient. In addition, Islamic religious education aims to develop attitudes and characters that are loyal and pious to Allah SWT and in line with current reality. All educational institutions must be proactive, creative and productive in reading the phenomena that occur today. Therefore, the role of IT is very important here, creating good designs as a foundation for the advancement of information and communication technology, as well as adding Islamic religious education learning activities with materials and skills and practicing religion including learning activities and mastery. However, we must also be able to use a technical approach with a learning method using the